Phytochemical study of the alkaloids from the bulbs of Eucharis grandiflora Planchon (Fam. Amaryllidaceae) - Garcia, Ma. Victoria G.
The study covers the extraction of the alkaloid from the bulbs of Eucharis grandiflora Planchon (Fam. Amaryllidaceae) using a polar solvent, ethanol. A phytochemical study was made on the concentrated ethanol extract by thin layer chromatography and determination of melting point of the isolated crystals from the preparative chromatography.